SOSIALISASI NILAI-NILAI KULTURAL DALAM KELUARGA Studi Perbandingan Sosial-Budaya Bangsa-Bangsa - Syarif, Jamal (Sabda: Jurnal Kajian Kebudayaan, 2012)
This article presents a comparative study of the socialization of values, norms and practices in various communities around the world. The materials of the study are obtained from the results of the socialization in the family in different countries. In most societies in the world, family holds a central position as the primary agent of socialization. Family has a significant role to prepare individuals in the early period of the development of its members. It is expected that family members have an active role in the community they live in. Values, norms and practices embedded in primary socialization are affected by family background involving ethnic, religion, culture and social strata.